Understanding China's industrialization driven water pollution stress in 2002–2015—A multi-pollutant based net gray water footprint analysis. (15th May 2022) - Yang, Zhongwen; Li, Bin; Xia, Rui; Ma, Shuqin; Jia, Ruining; Ma, Chi; Wang, Lu; Chen, Yan; Bin, Lingling
Abstract: China produces a large amount of industrial effluent with multiple pollutants contained, along with a flourishing economy. This study aims to examine the dynamics between China's industrialization and accompanying environmental pressure based on the gray water footprint (GWF) concept. A newly proposed net GWF (NetGWF) and the decoupling index (DI) are applied to evaluate China's industrial activities during 2002–2015 in different modes considering typical, all, and individual pollutants. The NetGWF dynamics are further quantitatively decomposed into 17 effects of not only commonly assessed drivers but also industrial fixed capital formation, inventory variation, and import, using an advanced dynamic decomposition analysis approach. Results show NetGWF is an effective indicator measuring domestic water pollution stress from industrialization, with NetGWF-AllPlt (estimated using all pollutants) validated to be more reliable and sensitive than NetGWF-COD&NH3N (estimated using Chemical oxygen demand and Ammonia nitrogen). An overall decoupling between China's industrialization and wastewater pollution is identified with most of DIs less than 1.0 caused mainly by decreased (by around 40%) industrial NetGWFs for 2002–2015. Industrial fixed capital formation and export have caused main components of China's industrial GWF, with proportions of 37.3% and 30.8%, respectively, followed by urban household consumption (16.8%). Volatile phenol, Petroleum, and Ammonia nitrogen are recognized as three decisive contaminants to the industrial NetGWFs. Technological development is the dominant contributor (−50%) to decreasing China's industrial NetGWFs, while fixed capital formation (18%) and export (16%) are principal drivers increasing the NetGWFs. Based on these, we expect to provide informative findings for building a pollution-decoupled industrialization. Highlights: NetGWF is effective in measuring domestic water pollution stress. Implies an overall decoupling of industrialization and effluent pollution. Industrial fixed capital formation and export are main sources of pollution stress. Volatile phenol, Petroleum, and NH3N are decisive pollutants of NetGWF. 17 drivers behind evolving industrial NetGWFs are quantitatively examined.